Effects of osteoporosis education intervention on knowledge, belief and selfefficacy among female academicians in a public university in Malaysia - Amin, Samia (2018)
Background: Osteoporosis is a global health problem which not only causes increase economic burden, but also leads to social, physical and psychological consequences. It is chronic health problem which is characterized by decreased bone mass density, micro architectural deterioration of bone tissue and fragility fractures, particularly to the hip, spine, wrist and shoulder. It is a silent undiagnosed disease until a fracture occurs due to an accidental fall. Worldwide osteoporosis causes more than 8.9 million fractures annually, resulting in an osteoporotic fracture every 3 seconds. Although it can affect either gender, 80% of those affected are women. Objective: The objective of this study was to develop and evaluate the effect of an educational intervention based on Health Belief Model to improve knowledge, beliefs and self-efficacy regarding osteoporosis among female academician in Universiti Putra Malaysia. Method: This study was single blinded randomized controlled trial. The study population was full time female academician in Universiti Putra Malaysia. Sampling unit was individual female academician in Universiti Putra Malaysia. A multi-stage random sampling was used. Female academic respondents of different faculties were randomized into intervention and control group. All female academicians were invited to participate in the study with informed consent form. Health Belief Model was used as theoretical framework. To measure Osteoporosis Knowledge Test (OKT), Osteoporosis Self- Efficacy Scale (OSES) and Osteoporosis Health Belief Scale (OHBS), data were collected on socio-demographic background, knowledge, beliefs and self-efficacy on osteoporosis. An educational intervention of three months duration (12 weeks) was given with a follow up motivational sessions by telephone. The control group received the same educational intervention material after the completion of the study. To evaluate the effect of the intervention, data were collected at baseline, immediately, one month and three months after intervention for both groups. Descriptive and multivariate statistics (GLM) were used for analyzing the data using SPSS version 21 and the significance level was set at P<0.05. In this study a per protocol analysis was done that included only those participants who completed the protocol for the intervention that they were originally allocated. Result: Six hundred and twenty-four female academicians were screened at their respective faculties. Response rate was 91% at baseline. Finally, the number of participants during study period was 212 at baseline (114 in the intervention and 98 in the control), 201 immediately (108 in the intervention and 93 in the control), 193 at one month (103 in the intervention and 90 in the control) and 193 participants (103 in the intervention and 90 in the control group) who completed the three months post intervention assessment. The mean age of participants was 37.1 years (SD=7.2) and majority of them were Malay (84%), married (88%) with tertiary education (90%). After intervention, from baseline to three months follow up there was a significant increase in the mean score of knowledge (20.7 - 28.3, p<0.001), beliefs (215.2 - 225.1, p<0.001) and self-efficacy (22.4 -25.9, p<0.001). The GLM model was applied to detect the differences in change within and between groups for continuous data from baseline to three months follow up and controlling for baseline socio-demographic data. The results show a significant difference between groups (F=173, p<0.001) and within groups for knowledge score (F=1009, p<0.001); between groups (F=8.403, p<0.001) and within groups for beliefs score (F=13.806, p<0.001); between groups (F=4.68, p<0.001) and within groups for self -efficacy score (F=9.73, p<0.001). Time and group interactions were insignificant (p = 0.221). Conclusion: These results provided evidence for the effectiveness of an educational intervention in promoting osteoporosis knowledge, beliefs and self-efficacy within female academician of University Putra Malaysia which suggests that increase knowledge on osteoporosis can improve exercise and calcium intake belief and selfefficacy even after three months of intervention, but policy should implement for long term intervention to sustain this effectiveness.